Cultural Ethos in Driving Learning Achievement: Research on Students of SMA Sutomo 1 Medan - Grace Prima Apriani Sihombing (SocioEdu: Sociological Education, 2026)
This study describes the cultural ethos that affects student achievement, where cultural ethos forms students' learning habits (habitus) so that it has an impact on student motivation in achieving achievement. This research was conducted using a correlational quantitative research method using the Pearson correlation test to determine the relationship between two variables, namely the cultural ethos variable (x) and student achievement (y). This study was conducted on 368 people consisting of students in grades X, XI, XII and alumni. Sampling procedures by means of systematic random sampling, data collection using questionnaires and data analysis is done univariate, bivariate with normality test and validity test. The results of this study found that there was an influence of the cultural ethos taught by students' families on improving students' learning achievement. High-achieving students recognise that the cultural ethos taught by their families provides motivation to be enthusiastic in learning and achieving. Interestingly, there is a form of application of cultural values passed down from generation to generation to students from both parents and grandparents to remind them to motivate them to be enthusiastic in pursuing their dreams and learning achievements.